2016
DOI: 10.5005/jp-journals-10005-1364
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Different Finishing and Polishing Devices on Nanofilled, Microfilled, and Hybrid Composite: A Scanning Electron Microscopy and Profilometric Study

Abstract: The continuous development of esthetically acceptable adhesive restorative material has made a variety of tooth-colored materials available for clinical use. The advent of visible light polymerizing resin and the use of finer filler particles permit resin composites to be polished to higher degree. The effect of polishing systems on surface finish has been reported to be material-dependent, and the effectiveness of these systems was mostly product-dependent. Hence, the purpose of this study was to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
77
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(102 citation statements)
references
References 93 publications
3
77
2
3
Order By: Relevance
“…Contrary to what was evidenced by Yadav, Raisingani, Jindal, and Mathur () in relation to the poorer finishing/polishing response of the Filtek Z250 XT composite compared to other micro and nanoparticles, in the present study, the Filtek Z250 XT stood out in the finishing/polishing and finishing/polishing groups plus additional polishing by the lower mean roughness values. This contradictory behavior is possibly due to the interaction of this composite with the finishing and polishing systems used in the present study, which may not promote a removal of the composite particles such as Sof Lex Pop‐On used by Yadav et al ().…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to what was evidenced by Yadav, Raisingani, Jindal, and Mathur () in relation to the poorer finishing/polishing response of the Filtek Z250 XT composite compared to other micro and nanoparticles, in the present study, the Filtek Z250 XT stood out in the finishing/polishing and finishing/polishing groups plus additional polishing by the lower mean roughness values. This contradictory behavior is possibly due to the interaction of this composite with the finishing and polishing systems used in the present study, which may not promote a removal of the composite particles such as Sof Lex Pop‐On used by Yadav et al ().…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to what was evidenced by Yadav, Raisingani, Jindal, and Mathur () in relation to the poorer finishing/polishing response of the Filtek Z250 XT composite compared to other micro and nanoparticles, in the present study, the Filtek Z250 XT stood out in the finishing/polishing and finishing/polishing groups plus additional polishing by the lower mean roughness values. This contradictory behavior is possibly due to the interaction of this composite with the finishing and polishing systems used in the present study, which may not promote a removal of the composite particles such as Sof Lex Pop‐On used by Yadav et al (). As the granulation of the Sof Lex Pop‐On system (Red 17.01 μm; Medium Orange 7.01 μm; Light Orange 5.72 μm; Yellow 1.68 μm) (Yadav et al, ) is larger than the system in this work, it is probable that the removal of particles of charge is greater by the one, which, consequently, favors an increase in the surface roughness (Figure ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It has been previously shown that the PoGo finishing and polishing systems generated a greater surface roughness of the Z250 resin when compared to the Soflex type, disagreeing with our results where no difference was observed between the groups. This may be explained because the Z250 resin is a micro-hybrid resin, and larger particles offer less protection on the resin matrix from a finishing and polishing process [20].…”
Section: Discussionmentioning
confidence: 99%